A systematic investigation of the short and long term experiences of taking part in research about suicidal thoughts and acts in the context of a randomised controlled trial - Sarah Peters; Leanne Cook; Donna Littlewood; Yvonne Awenat; Richard Drake; Jodie Gill; Anna Gorton; Gillian Haddock; Kamelia Harris; Kerry Hozhabrafkan; Charlotte Huggett; Lauren Kirby; et al. (Elsevier, 2022)
Partaking in studies about suicide can be a positive experience. There is also evidence of some negative impacts in the days immediately following participation. No research has examined both the short and longer term effects of repeated assessment of an individual's suicidal thoughts/behaviours. Clinical trials can involve multiple suicide assessments over several months. The current study investigated whether participants experienced any brief or lasting effects from this kind of intense suicide focused research. Participants had recent suicidal experiences, and were participating in a randomised controlled trial evaluating a psychological therapy targeting suicidal experiences for people with non-affective psychosis. Multiple measures of suicidal thoughts/acts were completed at baseline, 6 and 12-month follow-up time-periods. For the current study, participants (N ​= ​100 ​at baseline and n ​= ​32 ​at follow-up) undertook a semi-structured qualitative interview about their experiences of taking part in suicide research, and completed a checklist of adjectives to describe how it felt to talk about suicide during the assessments. They rated their current mood before and after completing the trial assessments using a visual analogue scale. A convergent mixed methods approach indicated that participation was positive in both the short and longer term. Mood improved or did not change over the course of assessments. More positive than negative adjectives were selected, regardless of the severity of suicidal thoughts experienced by participants. Thematic analysis of the qualitative data revealed many benefits of participating, including catharsis, being able to help others and being part of a wider endeavour to understand suicidal experiences. Both short and longer term feelings of distress arising from participation were offset by the expectation and acceptance of this occurring, together with the application of participant-initiated coping strategies. These findings lend reassurance that inviting people with severe mental health problems to participate in suicide research is not detrimental in either the short or long-term.